Genomic diversity and phylodynamic of bovine viral diarrhea virus in Argentina - Spetter, Lucas Maximiliano; Louge Uriarte, Enrique Leopoldo; Verna, Andrea Elizabeth; Leunda, Maria Rosa; Pereyra, Susana Beatriz; Odeon, Anselmo Carlos; Gonzalez Altamiranda, Erika (Elsevier, 2022)
Bovine viral diarrhea virus (BVDV) is an important pathogen of ruminants worldwide and is characterized by high genetic diversity and a wide range of clinical presentations. In Argentina, several studies have evaluated the genetic diversity of BVDV but no phylodynamic study has been published yet. In this study, a comprehensive compilation and update of Argentinean BVDV sequences were performed, and the evolutionary history of BVDV was characterized by phylodynamic analyses based on the 5´UTR. Although BVDV-1b and BVDV-1a were the most frequent subtypes, novel subtypes for Argentina, 1e and 1i, were identified. The phylodynamic analysis suggested that BVDV started its diversification in the mid-1650s with an exponential increase in viral diversity since the late 1990s, possibly related to the livestock expansion and intensification in the country. Evolutionary rate in the 5´UTR was faster for BVDV-1a than for BVDV-1b, and both subtypes presented an endemic nature according to the demographic reconstructions. The current study contributes to clarify the evolutionary history of BVDV in the main cattle region of the country and provides useful information about the epidemiology and future development of diagnostic and control tools in Argentina.